A Periplasmic Photosensitized Biohybrid System for Solar Hydrogen Production - Luo, Bifu; Wang, Yan‐Zhai; Li, Di; Shen, Hongqiang; Xu, Li‐Xia; Fang, Zhen; Xia, Zhenglong; Ren, Jianlin; Shi, Weidong; Yong, Yang‐Chun (Advanced energy materials, 2021)
Whole‐cell inorganic‐biohybrid systems, integrating inorganic photosensitizers with intact living cells, have shown great potential for solar hydrogen production. However, the typical whole cell biohybrid system often suffers from the sluggish kinetics of electron transfer in the transmembrane diffusion process, which severely restrict their photocatalytic activity. Here, a unique periplasmic photosensitized biohybrid system is constructed by translocating CuInS2/ZnS quantum dots (QDs) into the Shewanella oneidensis MR‐1 (SW) cells that express periplasmic hydrogenases. The photoexcitation and electron transfer processes of QDs photosensitizers occur simultaneously in the periplasm of SW cells, which reduces the distance for electron transport and avoids the extra energy loss involved in the transmembrane process. As expected, the photocatalytic H2 generation of the fabricated biohybrid system is 8.6 times higher than that of bare QDs under visible light irradiation. Moreover, the good viability and stability of this biohybrid system endow it with an excellent sustained hydrogen production within 45 h, representing the most stable biohybrid among the reported whole‐cell biohybrid H2 production systems. This work provides a novel insight into the construction of a robust whole‐cell biohybrid system for solar hydrogen production. This work reports an intracellular quantum dots photosensitized biohybrid system for realizing an enhanced solar hydrogen production activity. Low toxicity and good biocompatibility of CuInS2/ZnS quantum dots (QDs), as well as the low damage of visible light to bacteria is helpful for increasing long‐term stability, which surpasses most reported whole cell biohybrid systems.